2021
DOI: 10.3390/ijms22179526
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Inhibitors for Treating Locally Advanced/Metastatic Bladder Urothelial Carcinomas via Dual Targeting of Tumor-Specific Oncogenic Signaling and the Tumor Immune Microenvironment

Abstract: Locally advanced or metastatic urothelial bladder cancer (a/m UBC) is currently treated using platinum-based combination chemotherapy. Immune checkpoint inhibitors (ICIs) are the preferred second-line treatment options for cisplatin-eligible a/m UBC patients and as first-line options in cisplatin-ineligible settings. However, the response rates for ICI monotherapy are modest (~20%), which necessitates the exploration of alternative strategies. Dysregulated activation of fibroblast growth factor receptor (FGFR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Growing evidence suggests that FGFR GAs are associated with worse outcomes in different tumor types [ 14 , 15 , 16 ]. In spite of the general correlation of FGFR GA with lower grades and stages of nonmuscle-invasive UC, there is no evidence to support that FGFR GAs are associated with a favorable phenotype once urothelial carcinoma advances [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that FGFR GAs are associated with worse outcomes in different tumor types [ 14 , 15 , 16 ]. In spite of the general correlation of FGFR GA with lower grades and stages of nonmuscle-invasive UC, there is no evidence to support that FGFR GAs are associated with a favorable phenotype once urothelial carcinoma advances [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic overexpression of FGF1 has been shown to be highly associated with cancer progression and prognosis in bladder cancer [39] . Recent studies have demonstrated that FGF inhibitors can be used to treat locally advanced/metastatic UC by targeting tumor-specific oncogenic signaling involving the tumor immune microenvironment [40] . Additionally, LRRC59 is necessary for the nuclear import of oncoprotein protein phosphatase 2A (PP2A, CIP2A) [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor vasculogenesis is a complex process driven by the VEGF, PDGF, EGF, FGF, and ANG families, with VEGF-VEGFR and FGF2-FGFR1/2 signaling playing key roles by promoting endothelial cell proliferation and migration, duct formation, and protease production [ 18 , 144 146 ]. Assays on murine brain capillary endothelial cells (MBEC) point to enhanced chemotaxis of MBEC by FGF2/FGFR, an effect is associated with MAPK signaling [ 17 , 147 ].…”
Section: Fgf/fgfr Signaling and Tmementioning
confidence: 99%
“…FGFR-TKI induces normalization of the tumor vascular system, which is a prerequisite for the extravasation of immune cells and T-lymphocyte infiltration [ 144 , 145 , 162 ]. Anti-angiogenic therapy including anti-FGF signaling has been well-documented in numerous studies to enhance the efficacy of immunotherapy [ 163 166 ].…”
Section: Immunological Effects Of Fgfr-tkimentioning
confidence: 99%